2017
DOI: 10.1016/j.jece.2017.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ammonia in the anaerobic digestion of food waste

Abstract: Ammonia toxicity was investigated in mesophilic (37 o C) and thermophilic (55 o C) digesters using high and low-nitrogen food wastes (FW). Mesophilic inoculum was successfully acclimated to thermophilic conditions by a step change in temperature followed by incremental increases in organic loading rate (OLR). Digestion performance and stability were monitored via volatile fatty acid (VFA) profiles, alkalinity, specific methane production (SMP) and volatile solids (VS) destruction. High-nitrogen mesophilic dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The inhibitory effect of urea, NH 4 Cl, TAN, FAN and high N concentration in feeding, as well as the effect of elevated ammonium (NH 4 + ), elevated ammonium nitrogen (NH 4 + -N) and elevated TAN on biogas and methane yields, have been previously studied [1,4,15,17,22,32,[51][52][53]. However, no results on the effects of N concentration in inoculum and N-increase rate in feedstock on the level of inhibition in specific methane yield were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory effect of urea, NH 4 Cl, TAN, FAN and high N concentration in feeding, as well as the effect of elevated ammonium (NH 4 + ), elevated ammonium nitrogen (NH 4 + -N) and elevated TAN on biogas and methane yields, have been previously studied [1,4,15,17,22,32,[51][52][53]. However, no results on the effects of N concentration in inoculum and N-increase rate in feedstock on the level of inhibition in specific methane yield were found.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of protein-rich substrates, such as kitchen waste, poultry manure, microalgae, green legumes, oilseeds, etc. may lead to high concentrations of nitrogen (N) in the reactor during anaerobic digestion (AD) [1][2][3][4]. High concentrations of N inside the reactor negatively affect process stability and efficiency due to ammonia formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was clearly demonstrated in a comparative study by Yirong et al (2013a) which showed the onset of failure in thermophilic SS-DFW digesters when TAN concentrations reached 3.0 g N L -1 . A parallel study with acclimatisation to thermophilic conditions using a low nitrogen (1.45 % of dry weight) synthetic food waste showed long-term stable operation was possible in thermophilic conditions, while subsequent increases in the nitrogen concentration by addition of urea to this feedstock confirmed that the critical TAN concentration was between 2.5-3.0 g N L -1 (Yirong et al, 2013b; VALORGAS, 2013), equivalent to FAN concentrations of 590-710 mg N L -1 at the operational pH. This threshold value is similar to that reported in other studies where suppression of methanogenic activity as a result of ammonia toxicity has been demonstrated in thermophilic systems (Angelidaki and To maximise the specific methane yield in thermophilic digestion of SS-DFW while avoiding VFA accumulation and process instability, one approach is to reduce the TAN concentration in the digester by gas stripping.…”
Section: Introductionmentioning
confidence: 94%
“…The treatment of wastewater with a low TOC/N ratio still represents a challenge for industrial wastewater treatment plant. Conventional biological processes, such as Anaerobic Digestion (AD), are generally unsuitable to complete the nitrogen cycle due to the inhibition of microorganisms involved in the treatment [12]. For this reason, effluents from AD are usually rich in ammonium up to 2 kgN/m 3 [13].…”
Section: No −mentioning
confidence: 99%